Peran Guru Pendidikan Agama Islam dalam Membentuk Kepribadian Siswa - Sri Wegawati; Syarifah Salmah; Rabiatul Adawiah; Ahmad Risman; Nizari Rahman; M. Zulfa Alfiannur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the role of Islamic Religious Education (PAI) teachers in shaping student personality at SMP Negeri 3 Kusan Hilir, Tanah Bumbu Regency; to identify the efforts made by these teachers in this process; and to determine the factors involved in shaping student personality at the school. The study employs a qualitative research design with a descriptive approach. The results indicate that the role of Islamic Religious Education teachers in shaping student personality at SMP Negeri 3 Kusan Hilir involves: a) analyzing the teacher's role in personality formation; b) analyzing the efforts undertaken by the teachers; and c) analyzing the factors involved in the process. The study concludes that the role of Islamic Religious Education teachers in shaping student personality at SMP Negeri 3 Kusan Hilir is crucial. Teachers do not merely act as instructors but are also capable of flexibly assuming various roles—serving as educators, parental figures, and friends to the students. Keywords: Islamic Religious Education Teacher, Student Personality